Subjective Wellbeing among High School Students: A Research on the Role of Emotional and Social Support - Nita Rohayati; Cempaka Putrie Dimala; Wina Lova Riza; Lania Muharsih (Edutran, 2023)
The government's policy regarding the resumption of face-to-face schooling requires students to adapt to a new learning system. The situation faced by students will impact their psychological state, including their subjective well-being. Several factors predicted to play a role in subjective well-being are emotional maturity and social support. This research aims to investigate the role of emotional maturity and social support in subjective well-being among high school students in Karawang. The method used is a quantitative method by distributing an online questionnaire using Google Forms. The scales used were the Subjective Well-being Scale, Emotional Maturity Scale, and Social Support Scale. The research participants consisted of 287 respondents from grades X, XI, and XII who had undergone face-to-face learning after the government-imposed activity restrictions. The results of the data analysis using multiple linear regression techniques showed an F-value of 27.762 with a significance value of 0.000 < 0.005, indicating that the hypothesis in this research is accepted. This means that the emotional maturity and social support variables, together, have an influence on subjective well-being.